Do Non-socially Responsible Companies Achieve Legitimacy Through Socially Responsible Actions? The Mediating Effect of Innovation - Blanco, Belen; Guillamón-Saorín, Encarna; Guiral, Andrés (2013)
This study investigates the effects on organization’s financial performances of, first, the extent to which the organizations are involved in controversial business activities, and second, their level of social performance. These companies can be considered non-socially responsible given the harmful nature of the activities they are involved in. Managers of these companies may still have incentives to pursue socially responsible actions if they believe that engaging on those actions will help them to achieve legitimacy and improve investors’ perception about them. We develop a comprehensive methodology to investigate these corporate social performance (CSP)-related effects in a complex but specific setting. To this end, we analyze a sample of 202 US firms for the period 2005–2008 using a novel method in this area: partial least squares. Our results indicate that, contrary to the general findings in prior literature, companies involved in controversial business activities which engage in CSP do not directly reduce the negative perception that stakeholders have about them. Instead, we found evidence of a positive mediation effect of CSP on financial market-based performance through innovation.
Keywords: partial least squares; Innovation intensity; Controversial activities; Financial Performance; Corporate Social Performance